Research of leakage characteristics of single screw refrigeration compressors with the Multicolumn Envelope Meshing Pair. (January 2015) - Wang, Zengli; Liu, Zhan; Wu, Weifeng; Feng, Quanke
Abstract: The Multicolumn Envelope Meshing Pair (MEMP) was proposed and has been applied for the single screw refrigeration compressor (SSRC) to reduce the wear of the meshing pair. However, the geometric model shows its changed shape of the leakage paths compared with the existing straight line envelope meshing pair (LEMP). It is necessary to research the leakage characteristics of the SSRC with MEMP and LEMP, to evaluate the value of the proposed MEMP. In this paper, the geometric model of the leakage paths between star-wheel and screw rotor is established. A two-phase leakage mathematical model for gas-oil flow is presented to predict the gas leakage rate of the SSRC with MEMP. The experiments of the performance of a SSRC with MEMP were conducted to verify the leakage mathematical model. Obtained results show the leakage of the SSRC with MEMP is a little bit smaller than that of the SSRC with LEMP. Highlights: The leakage areas of the radial and the radial leakage path have been calculated. The experiments of the performance of a SSRC with MEMP were conducted. The leakage flow rates at the both side of the tooth flank have been calculated. The leakage characteristics of SSRC with MEMP have been carried out. Replace the straight line envelope meshing pair by the MEMP is suggested.